Flipchart-Based Education Improves Antibiotic and Antimicrobial Resistance Knowledge Among Rural Elementary Students: A Pre-Experimental Study - I Gusti Ayu Rai Widowati; Ida Ayu Manik Partha Sutema; Ni Komang Semara Yanti; I Wayan Agus Gede Manik Saputra; Ni Nyoman Sri Budayanti (Jurusan Farmasi Universitas Negeri Gorontalo, 2026)
Antimicrobial resistance (AMR) remains a major public health challenge, driven in part by inappropriate antibiotic use and limited public understanding of antibiotics and AMR. Early educational interventions for school-aged children may offer a sustainable approach to strengthening antibiotic literacy and promoting responsible health behaviors. This study evaluated the effectiveness of a flipchart-based educational intervention in improving elementary school students’ knowledge of antibiotics and understanding of AMR in a rural area of Bali, Indonesia. A pre-experimental one-group pretest-posttest design was conducted among 76 students using a validated questionnaire covering basic antibiotic concepts, AMR mechanisms, and prevention strategies. The proportion of students categorized as having high knowledge increased from 19.7% (95% CI: 11.8–27.8) before the intervention to 63.8% (95% CI: 53.9–75.3) after the intervention, while the proportion with low knowledge decreased from 21.1% to 10.5%. Mean knowledge scores increased significantly from 58.82 ± 16.57 to 75.13 ± 18.00, with a mean difference of +16.32 (95% CI: 12.55–20.08; p 0.001). The intervention also demonstrated a large practical effect (Cohen’s d = 0.99). These findings indicate that flipchart-based education can effectively improve antibiotic knowledge and AMR understanding among rural elementary school students and may serve as a promising school-based health education approach to support early antibiotic literacy.